2019
DOI: 10.1016/j.conbuildmat.2019.01.174
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different monomer ratios and recycled concrete aggregate on mechanical properties and durability of geopolymer concretes

Abstract: Properties of geopolymer concrete using metakaolin (MK) as the aluminosilicate source and recycled concrete aggregate (RCA) as partial replacement of natural aggregate are presented in this paper. The effects of sodium silicate (SS) to sodium hydroxide (SH) ratios, and RCA in different percentages on the mechanical and durability properties of geopolymer concrete were determined. Microstructural changes of geopolymers as a result of using RCA were evaluated via scanning electron microscopic (SEM) images. Test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(53 citation statements)
references
References 68 publications
8
45
0
Order By: Relevance
“…conditions was on average about 35% higher than that under dry curing conditions. So, as expected, the curing regimes affect the compressive strength of concrete specimens [46][47][48][49][50][51] and the difference between wet and dry curing conditions can go up to 50% as reported by Mamola and Zaniewski [52]. Under wet curing conditions, the cube compressive strength of the control concrete was on average about 47.6% greater than that of RAC.…”
Section: Slumpsupporting
confidence: 66%
“…conditions was on average about 35% higher than that under dry curing conditions. So, as expected, the curing regimes affect the compressive strength of concrete specimens [46][47][48][49][50][51] and the difference between wet and dry curing conditions can go up to 50% as reported by Mamola and Zaniewski [52]. Under wet curing conditions, the cube compressive strength of the control concrete was on average about 47.6% greater than that of RAC.…”
Section: Slumpsupporting
confidence: 66%
“…During experimental studies, researchers revealed that the cement paste, including RHA, had a smaller quantity of calcium hydroxide because of the pozzolanic reaction [53]. Accordingly, the porosity and the content of portlandite in the ITZ are reduced in the composite; due to this, the width of this zone between the cement paste and the aggregate is also reduced [54,55]. Reportedly, the improvement in the concrete properties due to the addition of RHA particles has been mainly due to the creation of more C-S-H gels but low portlandite in the composite because of the interaction between the ash and the OHand Ca + ions, as well as calcium hydroxide [3].…”
Section: Pozzolanic Activitymentioning
confidence: 99%
“…As for GPC composed of metakaolin (MK) as an aluminosilicate source along with recycled concrete aggregate (RCA) as a partial alternative of natural aggregate, Koushbaghi et al [49] conducted a microstructural analysis to determine the effects of SS/SH ratio and RCA in diverse dosages on mechanical properties and GPC durability via scanning electron microscopic (SEM). Test results indicated that GPC compressive strength developed with an enhanced SS/SH ratio (Figure 6).…”
Section: Efficiency Of Alkaline Solution and Ambient Condition On Gpcmentioning
confidence: 99%